Humanizing Islamic Education for Autistic Children: A Case Study at State Special Schools - Ria Maharani; Martin Kustati; Nana Sepriyanti; Arsanur Rahman (Bustanul Ulum Journal of Islamic Education, 2026)
This study investigates the implementation of humanizing Islamic education for autistic children at Sri Soedewi Masjchun Sofwan State Special School. The study was motivated by the tendency of Islamic Religious Education to prioritize cognitive achievement while overlooking students emotional and psychological needs. Employing a qualitative case study approach, data were collected through in-depth interviews, participant observation, and documentation involving Islamic education teachers, assistant teachers, and parents of autistic students. The data were analyzed using thematic analysis through data condensation, data display, and conclusion drawing. The findings indicate that humanizing Islamic education was implemented through compassionate interaction, adaptive communication, emotional sensitivity, visual instruction, and repetitive learning strategies. Emotional comfort emerged as a prerequisite for students engagement in religious learning activities. Environmental and physiological factors, including dietary patterns, also influenced students concentration and classroom behavior. Despite these challenges, autistic students were able to participate in prayer practice, Qur’anic recitation, and religious habituation through patient guidance and collaboration between teachers and parents. This study is limited to one state special school and may not represent other inclusive educational settings